Beliefs about COVID-19 testing and treatment: A national survey of Black and White adults - Laura A. Siminoff; K. Laura Barker; Ryan Blunt; Diana Litsas; Gerard P. Alolod; Jay S. Patel (Public Health in Practice)
Objectives: Knowledge, access, and use of testing and antiviral treatments is critical to managing and mitigating the continuing burden of the novel Corona Virus (COVID-19) in the United States. This study measured knowledge, attitude, behaviors, and self-reported barriers towards COVID-19 testing and outpatient anti-viral medications (OPA) treatments among Black and older individuals who face greater hospitalization and mortality from the disease. Study design: Cross-sectional structured survey. Methods: Respondents were randomly selected from an opt-in national panel in December 2022. Equal numbers of Black and White US adults over the age of 40 (n = 1037) completed the 42 item online survey. The main measures were key sociodemographic variables of respondents, race, age, political affiliation and COVID-19 attitudes, beliefs, testing behaviors, and knowledge and barriers to OPA access. Results: Overall, awareness and knowledge of COVID-19 outpatient treatments was low. Black respondents were more likely to test for COVID-19 than White respondents but less likely to know about OPA treatments. Insurance coverage was a significant factor in use of home tests. Knowledge of OPA treatments was low across groups. White respondents were more likely than Black respondents to be aware of OPA treatments (1.75, 95 % CI [1.31–2.33]) as were higher income respondents (1.13, 95 % CI [1.08–1.17]) and self-identified Liberals (1.79, 95 % CI [1.29–2.49]). Conclusions: Clinicians should know large numbers of patients may not be testing for COVID-19, nor are they aware of outpatient treatment options and may hold inaccurate beliefs about them. Developing culturally specific patient education materials are warranted to increase testing, utilization of vaccinations and OPAs.